The Use of Conjunctival Staining to Measure Ocular Surface Inflammation in Patients With Dry Eye. Issue 6 (June 2019) - Yang, Soonwon; Lee, Hyun Jung; Kim, Da-Yeong; Shin, Soojung; Barabino, Stefano; Chung, So-Hyang
Abstract : Purpose: To investigate the expression levels of inflammatory cytokines in the conjunctival epithelium and correlations with clinical parameters in dry eye disease (DED). Methods: This study evaluated 28 patients with Sjögren syndrome (SS) DED, 28 patients with non-SS DED, and 10 controls. The messenger ribonucleic acid (mRNA) expression of inflammatory cytokines such as tumor necrosis factor-α, interleukin (IL)-1β, IL-6, interferon (IFN)-γ, IL-17, and matrix metalloproteinase 9 (MMP9) from conjunctival epithelium was investigated by real-time polymerase chain reaction. Protein expression was confirmed by immunofluorescence staining. Correlations were evaluated between the mRNA expression of inflammatory cytokines and clinical DED parameters such as ocular surface disease index score, Schirmer I value, tear film breakup time, and corneal and conjunctival staining scores. Results: Patients with non-SS DED expressed significantly more IFN-γ, IL-6, and MMP9 genes in the conjunctival epithelium than the controls ( P < 0.05), and all cytokine gene expression was significantly higher in patients with SS DED than in the controls ( P < 0.01). Tumor necrosis factor-α, IL-1β, IL-6, and IL-17 gene expression was higher in patients with SS DED than in the non-SS DED group ( P < 0.05). Immunofluorescence staining of conjunctival epithelium demonstrated that positive cells with IL-6 or MMP9 were significantly higher in non-SS DED than in controls ( P < 0.01) and much higher in SS DED than in non-SS DED ( P < 0.05). Conjunctival staining scores significantly correlated with the expression of IFN-γ, IL-6, IL-17, and MMP9 in both DED groups ( P < 0.05 in non-SS DED and P < 0.01 in SS-DED). Interestingly, correlation coefficients of all cytokines were much higher in SS DED compared to non-SS DED. Corneal staining scores showed positive correlations with IFN-γ, IL-17, and MMP9 ( P < 0.05), and correlation coefficients were lower than those of conjunctival staining scores. Conclusions: Conjunctival staining scores may be useful to measure ocular surface inflammation in SS and non-SS DED. Abstract : Supplemental Digital Content is Available in the Text.